Diagnostic accuracy of human epididymis secretory protein 4 for lung cancer: a systematic review and meta-analysis - Yan, Li; Hu, Zhi-De (Journal of Thoracic Disease, 2019)
Background: Several studies have assessed the diagnostic accuracy of serum human epididymis secretory protein 4 (HE4) for lung cancer, but their results were heterogeneous. The aim of this study was to systematically review the available studies and pool their results using meta-analysis. Methods: PubMed, EMBASE and Web of Science databases were searched up to January 1, 2019 to identify studies investigating the diagnostic accuracy of HE4 for lung cancer. We assessed the quality of eligible studies with the revised Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. The overall diagnostic sensitivity, specificity, positive and negative likelihood ratios were pooled using a bivariate model. Deeks’s test was applied to detect the degree of publication bias. Results: A total of 16 studies with 18 cohorts (1,756 lung cancers and 1,446 controls) were included. HE4 had a pooled sensitivity of 0.65 (95% CI: 0.54–0.75), specificity of 0.88 (95% CI: 0.82–0.92), positive likelihood ration of 5.3 (95% CI: 3.7–7.6) and negative likelihood ratio of 0.40 (95% CI: 0.30–0.52). Patient selection bias and partial verification bias were the major design weaknesses of available studies. No publication bias was observed. Conclusions: HE4 has moderate diagnostic accuracy for lung cancer. Its result should be interpreted in parallel with clinical findings and the results of other conventional tests. Further studies are still needed to rigorously evaluate the diagnostic accuracy of HE4 for lung cancer.